ANALISIS KONTRASTIF PENANDA NEGASI DALAM KALIMAT BAHASA PRANCIS DAN BAHASA INDONESIA - Arrasyid, Noor Diana (Universitas Ahmad Dahlan, 2022)
This study examines the peculiarities, similarities, and differences of negation patterns in French and Indonesian sentences. The data analyzed are declarative, interrogative, and negative imperative sentences taken from the Leipzig Corpora Collection. The analysis results found that there are similarities in the formation of negation markers in French “ne … jamais” and Indonesian negation markers “tidak pernah”. The equivalence also appears in the arrangement of negative imperative sentence markers, which are formulated with negative ne+adverbs pas+verb and jangan+verb. Regarding the differences, the negation marker in French is present in two mandatory components, while in Indonesian, it is marked with one marker. There is even more variety of negations in French. In Indonesian, there is a standard rule between the combination of negation markers and the type of predicate in a sentence, but French tends to be more accessible. The formation of past and passive negative sentences is also different. Finally, in negative imperative sentences in French, the verb that is negated must be conjugated according to the subject, but in Indonesian, this is not the case.